1998
DOI: 10.1038/nsb0198-19
|View full text |Cite
|
Sign up to set email alerts
|

Specific interactions between the syntrophin PDZ domain and voltage-gated sodium channels

Abstract: Syntrophins are modular proteins belonging to the dystrophin associated glycoprotein complex and are thought to be involved in the regulation of the muscular system. Screening of peptide libraries revealed selectivity of the synotrophin PDZ domain toward the motif R/K/Q-E-S/T-X-V-COO- found to be highly conserved in the alpha-subunit C-terminus of vertebrate voltage gated sodium channels (VGSCs). The solution structure of the domain in complex with the peptide G-V-K-E-S-L-V shows specific interactions between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
200
0

Year Published

1998
1998
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(215 citation statements)
references
References 32 publications
12
200
0
Order By: Relevance
“…In PSD-95 PDZ3, Arg-318 coordinates a water molecule that in turn stabilizes the negative charge on the bound carboxylate, together with the backbone amides (11). Harris et al (14) concluded that Lys-86 in ␣1-syntrophin PDZ is not involved in a direct ionic interaction with the peptide carboxylate, in agreement with the published structures (11,12,23,26,27) as well as our data. The equilibrium constant of ␣1-syntrophin PDZ domain binding to a C-terminal peptide is shown to display a salt dependence, with lower affinity at higher salt, similarly as PDZ3 in the present study (14).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In PSD-95 PDZ3, Arg-318 coordinates a water molecule that in turn stabilizes the negative charge on the bound carboxylate, together with the backbone amides (11). Harris et al (14) concluded that Lys-86 in ␣1-syntrophin PDZ is not involved in a direct ionic interaction with the peptide carboxylate, in agreement with the published structures (11,12,23,26,27) as well as our data. The equilibrium constant of ␣1-syntrophin PDZ domain binding to a C-terminal peptide is shown to display a salt dependence, with lower affinity at higher salt, similarly as PDZ3 in the present study (14).…”
Section: Discussionsupporting
confidence: 92%
“…Arg-318 is linked to the carboxylate of the peptide C-terminal valine via an ordered water molecule (11). Glu-373 of the ␣B helix corresponds to Asp-143 of the mouse ␣1-syntrophin PDZ that is known to form a salt bridge with a lysine residue at position Ϫ4 of its peptide (23). Kinetic experiments similar to those for the wild type were done on the mutants (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although syntrophins have been shown to bind directly to muscle Na V 1s (Gee et al, 1998;Schultz et al, 1998), their role in concentrating Na V 1s at the NMJ remains unclear. Interactions with syntrophin are not required for the association of Na V 1 with the plasma membrane (Adams et al, 2001).…”
Section: Stabilization Of Na V 1 Clusters At Maturing Nmjsmentioning
confidence: 99%
“…Binding studies show that both the first and second PDZ repeats in PSD-95 potently interact with the COOH-terminal tails of specific NMDA receptor subunits and other ion channels that terminate in a consensus Glu-(Ser/Thr)-X-(Val/Ile)-COOH (15)(16)(17)(18). Crystallographic studies have determined the structural design of this PDZ-peptide interface, which requires: 1) sequencespecific interactions and 2) peptide termination immediately following the valine (19,20). The fact that PSD-95 PDZ2 can interact with both COOH-terminal peptides and with the nNOS PDZ domain is intriguing.…”
mentioning
confidence: 99%